Molecular Mechanisms and New Treatment Paradigm for Atrial Fibrillation. (May 2016) - Sirish, Padmini; Li, Ning; Timofeyev, Valeriy; Zhang, Xiao-Dong; Wang, Lianguo; Yang, Jun; Lee, Kin Sing Stephen; Bettaieb, Ahmed; Ma, Sin Mei; Lee, Jeong Han; Su, Demetria; Lau, Victor C.; et al.
Abstract : Background—: Atrial fibrillation represents the most common arrhythmia leading to increased morbidity and mortality, yet, current treatment strategies have proven inadequate. Conventional treatment with antiarrhythmic drugs carries a high risk for proarrhythmias. The soluble epoxide hydrolase enzyme catalyzes the hydrolysis of anti-inflammatory epoxy fatty acids, including epoxyeicosatrienoic acids from arachidonic acid to the corresponding proinflammatory diols. Therefore, the goal of the study is to directly test the hypotheses that inhibition of the soluble epoxide hydrolase enzyme can result in an increase in the levels of epoxyeicosatrienoic acids, leading to the attenuation of atrial structural and electric remodeling and the prevention of atrial fibrillation. Methods and Results—: For the first time, we report findings that inhibition of soluble epoxide hydrolase reduces inflammation, oxidative stress, atrial structural, and electric remodeling. Treatment with soluble epoxide hydrolase inhibitor significantly reduces the activation of key inflammatory signaling molecules, including the transcription factor nuclear factor κ-light-chain-enhancer, mitogen-activated protein kinase, and transforming growth factor-β. Conclusions—: This study provides insights into the underlying molecular mechanisms leading to atrial fibrillation by inflammation and represents a paradigm shift from conventional antiarrhythmic drugs, which block downstream events to a novel upstream therapeutic target by counteracting the inflammatory processes in atrial fibrillation. Abstract : Supplemental Digital Content is available in the text.